The Effect Of Naturalist And Ecological Intelligence On Environmental Attitude Of High School Students - Fitria Meisarah; La Hasini; Sumarni Rumfot; Afrizal Afrizal; A. Hadian Pratama Hamzah (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat Lamongan, 2023)
The purpose of this study is to ascertain the relationship between ecological intelligence and naturalist intelligence and environmental care attitudes. At one of the senior high schools, this study was conducted in 2022. This research uses descriptive and quantitative data. Pupils in senior high school made up the study's population, and a sample of those pupils was selected at random. In order to collect data, a questionnaire instrument is used to assess ecological intelligence, naturalist intelligence, and environmental concern attitudes. Data analysis used multiple linear regression and was tested using SPSS. The findings demonstrated a significant relationship between ecological intelligence and naturalist intelligence and their impact on environmental care attitudes. The results of the F test demonstrate that ecological and naturalist intelligence combination have a favorable and significant impact on attitudes toward environmental care.